Infecção genital pelo HPV em adolescentes: diagnóstico biomolecular - Barros, Luiza Daura Fragoso de (2006)
The present study was to diagnose and classify the Human Papilloma Virus (HPV) in pregnant and non-pregnant adolescents, as study the risk factors related to the infection, identify the multiples oncogenics types presents in the study people and associate the differents types of HPV with cytology and colposcopy findings. Methodologic design: the type of study was prospective, descriptive and transversal coorte. Was study 111 sexually active adolescents, between 10 and 19 years old, patients of the Gynecology Service of the Professor Alberto Antunes University Hospital of the Federal University of Alagoas (HUPAA-UFAL). Was utilized the polymerase chain reaction / restriction fragment length polymorphism - sequencing (PCR/RFLPs) to identification of the virus. Results: the viral percentual in the inferior genital tract was 27% of the cases. The molecular genotyping revealed high risk viral genetic material - HPV 16, 33, 51, 58, 66, 1S39, CP8304 and LVX100, in 28,5% of the cases, low oncogenic risk - HPV 6, 11, 53, 61 e CP141, in 40% and, the other 31,4%, considered the indeterminate type, include high and low risk virus. This more incident type is found isolated or associated to other viral types and appears in 40% of the positive cases. The viral infection rate among the pregnant adolescents was 11,7%. The HPV genital infection was associated with a past of sexually transmitted diseases and the consumption of alcohol by the adolescent. The frequency of adolescents infected by HPV, associated to low grade intraepithelial lesion, was 5,0%. No associations were observed between the specific types of HPV and the cytology and colposcopy findings among the studied adolescents.